PENERAPAN MODEL SIMULASI ANTRIAN SINGLE CHANNEL SINGLEPHASE PADA ANTRIAN PELAYANAN MIXUE ICE CREAM & TEA - Salsabila Safitri; Lingga Perdananda; Ismi Nabilah; Renaldi Maulana Azani; Shofa, Mohamad Jihan (Metode : Jurnal Teknik Industri, 2024)
Queueing issues at an ice cream parlor in Serang City have led to long lines due to having only one service system. The queue problem arises when many customers request service, but the number of servers is limited. One issue is that customers often have to wait in line to be served by the cashier. The aim of this study is to develop strategies to reduce queue length and improve service efficiency. The method used is Discrete Event Simulation, which provides a reliable and measurable approach to model queue variations. This system allows for identifying the best solutions to reduce waiting time and increase service efficiency in the ice cream parlor industry. This study shows that with 30 data replications and using seconds as the time unit, the total queue waiting time is 7,215 seconds with an average of 510.59 seconds. The average waiting number in the queue is 2.2371. The result of 0.95 indicates that resource utilization is close to maximum (close to 1), meaning the resource is almost always in use.